Elevated cell‐free DNA in respiratory viral infection and associated lung allograft dysfunction. Issue 11 (5th August 2022) - Bazemore, Katrina; Permpalung, Nitipong; Mathew, Joby; Lemma, Merte; Haile, Betelihim; Avery, Robin; Kong, Hyesik; Jang, Moon Kyoo; Andargie, Temesgen; Gopinath, Shilpa; Nathan, Steven D.; Aryal, Shambhu; et al.
Abstract : Respiratory viral infection (RVI) in lung transplant recipients (LTRs) is a risk for chronic lung allograft dysfunction (CLAD). We hypothesize that donor‐derived cell‐free DNA (%ddcfDNA), at the time of RVI predicts CLAD progression. We followed 39 LTRs with RVI enrolled in the Genomic Research Alliance for Transplantation for 1 year. Plasma %ddcfDNA was measured by shotgun sequencing, with high %ddcfDNA as ≥1% within 7 days of RVI. We examined %ddcfDNA, spirometry, and a composite (progression/failure) of CLAD stage progression, re‐transplant, and death from respiratory failure. Fifty‐nine RVI episodes, 38 low and 21 high %ddcfDNA were analyzed. High %ddcfDNA subjects had a greater median %FEV1 decline at RVI (−13.83 vs. −1.83, p = .007), day 90 (−7.97 vs. 0.91, p = .04), and 365 (−20.05 vs. 1.09, p = .047), compared to those with low %ddcfDNA and experienced greater progression/failure within 365 days (52.4% vs. 21.6%, p = .01). Elevated %ddcfDNA at RVI was associated with an increased risk of progression/failure adjusting for symptoms and days post‐transplant (HR = 1.11, p = .04). No difference in %FEV1 decline was seen at any time point when RVIs were grouped by histopathology result at RVI. %ddcfDNA delineates LTRs with RVI who will recover lung function and who will experience sustained decline, a utility not seen with histopathology. Abstract : Among lung transplant recipients, increased levels of donor‐derived cell free DNA at the time of respiratory viral infection are associated with greater risk for CLAD stage progression and allograft failure in the following year, independent of time post‐transplant and the presence of respiratory symptoms.